plz answer soon tomorrow is exam plzzzzzzzzzzz

Asked by BhavSimran | 10th Mar, 2010, 12:05: PM

Expert Answer:

let angle C be acute, or obtuse.

draw AD perpendicuar to BC(or BC produced if necessary)

Now,

cosC =CD/CA

So

CD=CA cosC

let a=BC

b=CA

c=AB

then we get,

from this we can get the required result.

 note that going along  similar lines we can prove the result even if C is an obtuse angle.

Answered by  | 10th Mar, 2010, 03:50: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.